Design of SOPC digital frequency meter based on MicroBlaze. Issue 1 (January 2021) - Sun, Haixin; Fan, Yujie; Xiang, Qiang
Abstract: A method of SOPC implementation of digital frequency meter is presented in this paper. In the method, Encapsulated AXI IP core for frequency measurement and duty cycle measurement are configured with the embedded soft core MicroBlaze processor. The parameter measurement of the digital frequency meter is implemented by FPGA logic resources, and the measured data are transmitted to the soft core processor via AXI bus. The computation, control and display is completed by Microblaze soft core. The system is verified and tested on the Basys3 board card launched by digilent company. The results show that the system has the advantages of accurate measurement, good stability, simple scheme and low cost.